The Letters of Hildegard of Bingen : Volume II. - Hildegard, Saint, 1098-1179 (Oxford University Press, 1998)
This is the second volume in a translation (with full scholarly apparatus) of the entire correspondence of St Hildegard of Bingen (1098-1179). It comprises letters 91-217, in which Hildegard addresses lower-ranking spiritual leaders offering advice and consolation.